The Incidence and Classification of Adverse Drug Reactions at Bangrak STIs Center - Ma, Thanunyakorn; Chookiartsiri, Chantana; Daengsaard, Ekkachai; Tewthanon, Karunrat; Kittiyaowamarn, Rossaphorn (Journal of Health Sciences and Wellness, 2025)
Adverse drug reactions (ADRs) can occur following the use of medications for treatment, diagnosis, and disease prevention. In general, ADRs are divided into two types including side effect/Type A ADR and drug allergy/Type B ADR. This research is a retrospective descriptive research aimed to determine the incidence, frequency, and details of adverse drug reactions. Data was collected from May 2018 to December 2022 from the adverse drug reactions database of the Pharmacy Department at Bangrak STIs Center, a clinic providing outpatient services specifically for sexually transmitted diseases and dermatological conditions. The data collection tool used in this study was an adverse drug reaction recording form. The statistics used to analyze the data was descriptive statistics including frequency, percentage, mean, and standard deviation. The study found that out of 21,794 patients who received medication, 46 were new patients who experienced ADRs, an incidence rate of 0.21%. Most new patients who experienced ADRs were male (65.22%). The most common type of ADR was drug allergy/Type B ADR (70.83%). The drug class causing the most ADRs was Infections (65.31%), with doxycycline being the most common (36.73%). The most frequent ADRs involved the skin and subcutaneous tissue (53.23%). According to Naranjo's algorithm, the probability of ADRs was rated as probable (62.50%). Consequently, this research can create knowledge that supports the evaluation of the causality of ADRs associated with suspected medications used in the treatment of sexually transmitted infections and skin diseases. It also supports the surveillance and monitoring of ADRs among patients receiving diagnosis and treatment for these conditions.